Asymmetry flip in angle-resolved photoelectron spectra of rare gas atoms by intense circularly polarized few-cycle pulses - Fukahori, Shinichi; Yamanouchi, Kaoru; Paulus, Gerhard G. (Journal of Physics B-Atomic Molecular and Optical Physics, 2019)
We examine the phenomenon of the flip in the asymmetry in the emission direction of photoelectrons from rare gas atoms upon the ionization by a circularly polarized few-cycle laser field, and derive an analytical formula representing the photoelectron kinetic energy at which the asymmetry flip occurs based on the semiclassical tunnel ionization theory. We show that the energy at which the asymmetry flip occurs varies sensitively to the duration of few-cycle laser pulses and propose that the pulse duration can be determined experimentally using this analytical formula for the asymmetry flip energy.
CRIS-Team Scopus Importer:2023-04-20
Keywords: circularly polarized few-cycle pulses; pulse duration determination; tunnel ionization